2023
DOI: 10.1002/smll.202306738
|View full text |Cite
|
Sign up to set email alerts
|

Surface Engineering of Natural Killer Cells with CD44‐targeting Ligands for Augmented Cancer Immunotherapy

Sungjun Kim,
Shujin Li,
Ashok Kumar Jangid
et al.

Abstract: Adoptive immunotherapy utilizing natural killer (NK) cells has demonstrated remarkable efficacy in treating hematologic malignancies. However, its clinical intervention for solid tumors is hindered by the limited expression of tumor‐specific antigens. Herein, lipid‐PEG conjugated hyaluronic acid (HA) materials (HA‐PEG‐Lipid) for the simple ex‐vivo surface coating of NK cells is developed for 1) lipid‐mediated cellular membrane anchoring via hydrophobic interaction and thereby 2) sufficient presentation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Similarly, in our previous study, HA functional group-coated NK cells were tested with the CD44 blocking MDA-MB-231 model. The results showed comparable efficacy to uncoated NK cells when treated with MDA-MB-231 . This outcome provides evidence that the HA component of our coating material targets CD44 on cancer cell surfaces.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…Similarly, in our previous study, HA functional group-coated NK cells were tested with the CD44 blocking MDA-MB-231 model. The results showed comparable efficacy to uncoated NK cells when treated with MDA-MB-231 . This outcome provides evidence that the HA component of our coating material targets CD44 on cancer cell surfaces.…”
Section: Resultsmentioning
confidence: 53%
“…The results showed comparable efficacy to uncoated NK cells when treated with MDA-MB-231. 38 This outcome provides evidence that the HA component of our coating material targets CD44 on cancer cell surfaces. While HA moieties can enhance recognition and targetability toward CD44-overexpressing cancers, the facile incorporation of PEG and lipid into NK cell membranes allows for simple ex vivo cell surface modification.…”
Section: Preservation Of Various Intrinsic Properties Of Surface-coat...mentioning
confidence: 76%
“…This approach enables the augmented NK cell activation without the requirement of additional supplementary cytokine cocktails. Our results demonstrated that (1) TL modules could be effectively immobilized into the lipid bilayers of NK cell membranes, specifically via hydrophobic interaction [33,34], and (2) they could strengthen the membrane connections of NK cells through material-mediated physical links. In consequence, as compared with naturally-driven NK clustering, which is mediated by ECM production (without the aid of biomaterials), a significant induction of multiple membrane interactions occurred, leading to rapid and tight formation of NK cell clusters, and effective cell priming ultimately took place, resulting in enhanced IFN-γ secretion in TLNK spheroids.…”
Section: Discussionmentioning
confidence: 78%
“…It has been proposed that apoptosis is an important mechanism in NK cell-based immunotherapy . Perforin triggers the intrinsic pathway and elevates the release of cytochrome-c . FASL triggers the extrinsic apoptotic pathway by activating caspase-3. , To confirm the cell death mechanism, we examined the expression of apoptosis-related proteins (caspase-3 and cytochrome-c) using IHC staining.…”
Section: Resultsmentioning
confidence: 99%